The role of phagocytes in inflammatory bowel disease. - Hermanowicz, A; Gibson, P; Jewell, D (1985)
In recent years, almost all the emphasis in immunological studies of inflammatory bowel disease has been on specific, acquired immunity to various antigens. There is now increasing awareness that there is also a natural immune system composed of a family of natural effector cells. Natural reactivity appears spontaneously and plays a substantial role in resistance to disease. This review will present the function and role of granulocytes and monocytes/macrophages, important natural effector cells which may play a role in the pathogenesis of inflammatory bowel disease.